Cytokines in gingivitis and periodontitis: from pathogenesis to therapeutic targets - Neurath, Nicole; Kesting, Marco (Frontiers in Immunology, 2024)
Chronic inflammatory processes in the oral mucosa and periodontitis are common disorders caused by microflora and microbial biofilms. These factors activate both the innate and adaptive immune systems, leading to the production of pro-inflammatory cytokines. Cytokines are known to play a crucial role in the pathogenesis of gingivitis and periodontitis and have been proposed as biomarkers for diagnosis and follow-up of these diseases. They can activate immune and stromal cells, leading to local inflammation and tissue damage. This damage can include destruction of the periodontal ligaments, gingiva, and alveolar bone. Studies have reported increased local levels of pro-inflammatory cytokines, such as interleukin-1beta (IL-1beta), tumor necrosis factor (TNF), IL-6, IL-17, and IL-23, in patients with periodontitis. In experimental models of periodontitis, TNF and the IL-23/IL-17 axis play a pivotal role in disease pathogenesis. Inactivation of these pro-inflammatory pathways through neutralizing antibodies, genetic engineering or IL-10 function has been demonstrated to reduce disease activity. This review discusses the role of cytokines in gingivitis and periodontitis, with particular emphasis on their role in mediating inflammation and tissue destruction. It also explores new therapeutic interventions that offer potential for research and clinical therapy in these chronic inflammatory diseases.